2010
DOI: 10.1111/j.1365-2133.2010.09861.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis and the risk of cancer: a nationwide population-based cohort study

Abstract: Systemic sclerosis is a risk factor for cancer, particularly smoking- and alcohol-related cancers. Men with systemic sclerosis generally are at higher cancer risk than women. Both primary and secondary cancer preventive measures are needed in the care of patients with systemic sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 30 publications
6
87
1
10
Order By: Relevance
“…In addition, acquired lung diseases like obstructive and fibrotic lung diseases (e.g. chronic obstructive pulmonary disease [COPD], idiopathic pulmonary fibrosis and systemic sclerosis) are associated with increased risk of lung cancer [20][21][22].…”
Section: Etiology Of Lung Cancermentioning
confidence: 99%
“…In addition, acquired lung diseases like obstructive and fibrotic lung diseases (e.g. chronic obstructive pulmonary disease [COPD], idiopathic pulmonary fibrosis and systemic sclerosis) are associated with increased risk of lung cancer [20][21][22].…”
Section: Etiology Of Lung Cancermentioning
confidence: 99%
“…In many cohort, prospective, retrospective, and case control studies, hematological cancers such as non-Hodgkin lymphoma, leukaemia, multiple myeloma, and myeloproliferative neoplasms were reported in patients with SSc (3-6). A 2.5-fold increased risk for hematological cancers in a nationwide population-based cohort study was reported by Olesen et al (8) Paraneoplastic scleroderma may accompany hematologic malignancies (3,4). An increased risk for non-Hodgkin lymphoma was reported in female patients with SSc (1).…”
Section: Case Presentationmentioning
confidence: 90%
“…Szekanecz et al (3) observed that malignancy occured 6.6 years after the diagnosis of SSc. Diffuse cutaneous SSc compared with localised cutaneous SSc and male patients compared with female patients have a higher cancer risk (8). However, it has been reported that cancer incidence based on gender is controversial (2).…”
Section: Case Presentationmentioning
confidence: 99%
See 2 more Smart Citations